Observaciones del parasitismo de Palmistichus elaeisis (Hymenoptera: Eulophidae) sobre pupas de Quadrus cerialis (Lepidoptera: Hesperiidae) en Piper reticulatum (Piperaceae) en la Reserva Biológica Dr. Rodrigo Tarté, Ciudad del Saber, Panamá. - Murgas, Alonso Santos (2022)
As far as we can increase the knowledge about parasitoids or any natural enemy of plagues, contributions are relevant. These groups of insects have an important value, since the help to maintain insect population equilibrium and specially insects that are also plagues in different terrestrial ecosystems. The aim of this work is to report for the first time the parasitoid Palmistichus elaeisis (Hymenoptera: Eulophidae) in pupae of the butterfly Quadrus cerialis (Lepidoptera: Hesperiidae) over seedlings of Piper tuberculatum. These biological observations were made in the Biological Reserve Dr. Rodrigo Tarté, City of Knowledge, Panama province. Six seedlings of Piper reticulatum (Piperaceae); with a mean height of 0.5-1.0 meters, it was located in an open area on the sides of the path, asphalt road inside the Reserve (City of Knowledge). The material was collected and placed in insect hatching cages in order to maintain the leaves in adequate conditions so that the insects (larvae and pupae) could complete their development. Incubations temperature was 25± 2 °C with a photoperiod of 12:12 hour/light. Obtained parasitoids were labeled and preserved in ethanol 70%. As result 6 individuals of Q. cerialis were obtained in the biological reserve Dr. Rodrigo Tarté, City of Knowledge; 3 larvae and 2 pupae were obtained, 5 adults of Q. cerialis and from one pupae, 12 females and 2 males of the parasitoid Palmistichus elaeisis (Hymenoptera: Eulophidae); the parasitized pupae of Q. cerialis, presented a dark coloration, obvious sign that it was parasitized. The biological control exerted by P. elaeisis on Q. cerialis pupae could be an alternative to the use of chemical pesticides, which are widely used in agricultural systems to combat pests, such as the Lepidoptera species that roll or fold the leaves in agricultural crops, as is the case of Q. cerialis (Hesperiidae).